(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2016)
Social security, as one of the pillars of social security, is contributory and compulsory. Its purpose is to support individuals in special situations, whether present or future, listed by law, and it functions as an insurance mechanism designed to cover the basic needs of citizens in the event of any social contingency. The aim of this study is to understand the impact that crimes against social security have on both the state that administers it and the society that funds it. Within this scope, criminal conduct will be addressed and analyzed, as well as criminal repression in crimes against social security, considering that criminal law, which should be the ultima ratio, has been used as a reinforced form of tax enforcement.